2016
DOI: 10.1021/jacs.6b03760
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Reactivity of Fe8Me12 : Kochi’s S = 1/2 Species in Iron-Catalyzed Cross-Couplings with MeMgBr and Ferric Salts

Abstract: Iron-catalyzed cross-couplings with simple ferric salts have been known since the 1970s, pioneered by Kochi for cross-coupling using alkylmagnesium nucleophiles including MeMgBr. While Kochi observed the formation of a S = 1/2 iron species in reactions of simple ferric salts with MeMgBr proposed to be an iron(I) species, the identity of this species has remained undefined for nearly 40 years. Herein, we report the isolation and characterization of [MgCl(THF)5][Fe8Me12], which combined with EPR and MCD studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 24 publications
7
82
0
3
Order By: Relevance
“…4851 In particular, freeze-trapped 57 Fe Mössbauer spectroscopy has been demonstrated to serve as a powerful complement to traditional analyses of organic product distributions to correlate formation and consumption of iron intermediates with product generation. Use of this approach has generated unprecendented insight into the principles governing reactivity within iron-catalyzed cross-coupling methods using aryl nucleophiles, enabling the identification of iron(II) active species in iron-SciOPP catalyzed cross-couplings of alkyl halides with mesitylmagnesium bromide (MesMgBr) 48 and phenyl nucleophiles (phenylmagnesium bromide (PhMgBr) and activated phenyl borates).…”
Section: Introductionmentioning
confidence: 99%
“…4851 In particular, freeze-trapped 57 Fe Mössbauer spectroscopy has been demonstrated to serve as a powerful complement to traditional analyses of organic product distributions to correlate formation and consumption of iron intermediates with product generation. Use of this approach has generated unprecendented insight into the principles governing reactivity within iron-catalyzed cross-coupling methods using aryl nucleophiles, enabling the identification of iron(II) active species in iron-SciOPP catalyzed cross-couplings of alkyl halides with mesitylmagnesium bromide (MesMgBr) 48 and phenyl nucleophiles (phenylmagnesium bromide (PhMgBr) and activated phenyl borates).…”
Section: Introductionmentioning
confidence: 99%
“…Although several later studies arrived at the same conclusion, others suggested the formation of iron intermediates in lower or higher oxidation states . Notwithstanding these discrepancies, the discussion focused almost completely on mononuclear complexes before Neidig and co‐workers very recently proposed the involvement of small iron clusters as a “new paradigm … in this chemistry” . Studying the reactions of Fe III salts with MeMgBr in tetrahydrofuran (THF), these authors isolated and structurally characterized the unprecedented ionic cluster compound [MgCl(THF) 5 ] + [Me 12 Fe 8 ] − (Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Originally developed by Kochi in the 1970s, recent studies have identified [Fe 8 Me 12 ] − as the key reactive iron species formed in these reactions with MeMgBr (Scheme 1). [3] In 1998, Cahiez and Avedissian overcame many of the limitations of the Kochi ferric salt system through the use of N -methylpyrrolidone (NMP) as a co-solvent. [4] With NMP present, cross-couplings of various vinyl halides and alkyl Grignard reagents could be achieved with high chemoselectivity without the requirement of excess alkenyl halide (required in the absence of NMP), enabling preparative scale iron-catalyzed cross-coupling reactions (Scheme 1).…”
mentioning
confidence: 99%
“…While previous studies demonstrated that generation of [Fe 8 Me 12 ] − could be accomplished by reacting Fe(acac) 3 with 20 equiv of MeMgBr, [3] it was important to directly evaluate if the Cahiez protocol involving NMP has any effect on cluster formation. The addition of 20 equiv of MeMgBr to a 3 mM solution of 57 Fe(acac) 3 in 1:1 THF/2-MeTHF with 180 equiv of NMP (9 equiv of NMP relative to Grignard reagent; Cahiez protocol ratio [4] ) at RT led to the rapid formation of a pale yellow solution.…”
mentioning
confidence: 99%